Epidemiology of Pediatric Intensive Care Unit Admissions and Predictive Value of PEWS Score at Manipal Teaching Hospital, Pokhara: A 12-Month Observational Study - Timilsina , Mukunda; Basnet , Sahisnuta; Hirachan , Bikram (Nepal Journal of Medical Sciences, 2025)
Introduction: Pediatric Intensive Care Units (PICUs) play a crucial role in managing critically ill children, providing specialized life support and intensive monitoring. In Nepal infectious diseases, malnutrition, and limited access to healthcare are the primary drivers of pediatric critical illness. This study aims to assess the causes of PICU admissions and evaluate outcomes at Manipal Teaching Hospital (MTH) in Pokhara, Nepal. Methods: This was a hospital-based, cross-sectional observational study conducted at MTH, Pokhara, Nepal, from October 2023 to September 2024. A total of 355 pediatric patients, aged 1 month to 15 years, were included. Sociodemographic details, clinical findings, and laboratory results were recorded through structured proformas and analyzed with SPSS. Results: The average age of patients was 47.04 months (± 45.35), with 56.34% males and 43.66% females. Of the 355 patients, Pneumonias were the most common diagnosis 122 (34.4%), followed by sepsis 78 (22%) and status epilepticus 38(10.7%). The study found that 87.61% of patients improved, 7.61% left against medical advice, 2.54% died, and 2.25% were referred to other centers. Mortality was significantly higher among those diagnosed with pneumonia (p-value 0.05). The ROC curve showed an area under the curve (AUC) of 0.77, indicating that the PEWS score is an acceptable predictor of mortality in the PICU setting. Conclusions: This study observed Pneumonia to be a significant contributor to adverse outcome in PICU patients. PEWS score serves as an acceptable prognostic tool for predicting mortality risk in pediatric ICU patients, with higher scores indicating increased risk.